2020
DOI: 10.3390/su12030832
|View full text |Cite
|
Sign up to set email alerts
|

Circular Economy in China: Translating Principles into Practice

Abstract: The concept of circular economy (CE) has recently gained momentum in the political, scientific, and economic debate, especially in China and Europe. As a result, organizations and scholars have started to establish different sets of principles for its adoption. For this reason, it is important to identify and assess the differences and similarities among existing sets of CE principles, and how organizations and individuals understand and translate them into practice. In this paper, we firstly present a brief r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 84 publications
0
31
0
Order By: Relevance
“…However, since 1987, sustainability, in relation to businesses, has taken on the sense of being careful with the use of natural resources, beyond the relative scarcity expressed through prices [10]. There is also now a certain circularity in the use of these resources that refers to tasks not only of recycling but of transformation [11].…”
Section: Introductionmentioning
confidence: 99%
“…However, since 1987, sustainability, in relation to businesses, has taken on the sense of being careful with the use of natural resources, beyond the relative scarcity expressed through prices [10]. There is also now a certain circularity in the use of these resources that refers to tasks not only of recycling but of transformation [11].…”
Section: Introductionmentioning
confidence: 99%
“…The study evaluated the CE concept, as well as its limitations, in terms of environmental sustainability. Pesce et al identified the basic drivers and barriers to implementing CE principles at the corporate micro level and the organization of CE principles [11]. Beyond these examples, many other studies have considered specific CE cases [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…CE also attests to boost an economy development pattern harmonious with the environment (Murphy & Gouldson, 2000). Additionally, the public generally regards CE as an alternative form of economic mode aiming at decoupling global economic development from the finite resource consumption (Pesce et al, 2020). The essence of a CE economy is to minimize the consumption of resources and environmental costs to maximize economic benefits.…”
Section: Circular Economymentioning
confidence: 99%